Analysing Urban Land Use Change in GIS Environment - Ryngnga, Dr(Mrs)PK (International Journal of Scientific Research and Management (IJSRM), 2017)
Urban areas are growing at an unprecedented rate creating far-reaching urban landscapes. The gradual transformation from farmlands, forested areas into urban concrete landscape has caught the attention of urban planners and academicians. It is understood that in order to monitor and assess these gradual changes in urban environments, modern technology of remote sensing can provide better and efficient management. Therefore, this present paper emphasise the ability of the modern technology to map and monitor the spatial extent of the built environment, and associated temporal changes, which has important societal and economic relevance. Further, the paper underline the utility of Multi-temporal satellite data which can now provide the potential for mapping and monitoring urban land use change.